The webdoc as a tool in the struggle for equality: En la brecha (2018) by Lab RTVE - María Purificación SUBIRES MANCERA (Fonseca: Journal of Communication, 2019)
The webdoc, as an interactive and multimedia evolution of the cinematographic and television documentary, born with the development of the Internet, keeps the same essence of its precedents: its informative and denouncing character and its critical vision of reality. This paper analyses, using the case study methodology, the webdoc En la brecha, by RTVE Lab, which was created to celebrate the International Equal Pay Day, in 2018, and through which it was intended to denounce the existing salary gap –hence the title of the webdoc– between women and men in their average annual salary. At the same time, the webdoc also aims to make visible the work of women in those sectors in which they are under-represented, through the life experience and the testimony of seven women, of different professions. The project was not limited to showing these seven cases, but also offered other women the possibility to participate and contribute with their own experiences and opinions through the web –recorded by themselves, with a mobile or a webcam–. All the main protagonists and participants in the webdoc, as well as the director, are women.